The (Mis)use of the Man ‒ an Episode from the Life od Sveta Petronijević from the Novel The Third Spring by Dragoslav Mihailović - Stojković, Marijana B. (Collection of Papers of the Faculty of Philosophy in Priština, 2022)
At the heart of this research is the character of Sveta Petronijević from the novel The Third Spring by Dragoslav Mihailović. In this paper, an excerpt from the life of Sveta Petronijević will show how a small, provincial man, a person from the margins, is influenced by a powerful ideological mechanism that leads to his transformation and life tragedy. Under the influence of the ruling regime, the man is brought into a situation in which he is exploited, and must abide by the regime. Various interests, low passions and moral are stumbling blocks shown through the character of Sveta Petronijević, symbolically presenting him as a tragic and marginalised being in the universe pressed by the weight of ideology and system.
Keywords: Dragoslav Mihailović; The Third Spring; interpretation; tragedy; man; evil; ideology